Simvastatin Does Not Affect Vitamin D Status, but Low Vitamin D Levels Are Associated with Dyslipidemia: Results from a Randomised, Controlled Trial - Lars Rejnmark; Peter Vestergaard; Lene Heickendorff; Leif Mosekilde (International Journal of Endocrinology)
Objectives. Statin drugs act as inhibitors of the 3-hydroxy-3methylglutaryl coenzyme A (HMG-CoA) reductase enzyme early in the mevalonate pathway, thereby reducing the endogenous cholesterol synthesis. In recent studies, it has been suggested from epidemiological data that statins also may improve vitamin D status, as measured by increased plasma 25-hydroxyvitamin D (25OHD) levels. We now report the results from a randomised controlled trial on effects of simvastatin on plasma 25OHD levels. Design and Methods. We randomised 82 healthy postmenopausal women to one year of treatment with either simvastatin 40 mg/d or placebo and performed measurement at baseline and after 26 and 52 weeks of treatment. The study was completed by 77 subjects. Results. Compared with placebo, plasma levels of cholesterol and low-density lipoproteins decreased in response to treatment with simvastatin, but our study showed no effect of simvastatin on vitamin D status. However, plasma levels of triglycerides were inversely associated with tertiles of plasma 25OHD levels and changes in plasma triglycerides levels correlated inversely with seasonal changes in vitamin D status. Conclusion. Our data do not support a pharmacological effect of statins on vitamin D status, but do suggest that vitamin D may influence plasma lipid profile and thus be of importance to cardiovascular health.